2020
DOI: 10.1044/2020_ajslp-19-00179
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Scores: Using Converging Evidence to Determine Speech and Language Services Eligibility for Dual Language Learners

Abstract: Purpose Speech-language pathologists have both a professional and ethical responsibility to provide culturally competent services to dual language learners (DLLs). In this tutorial, we recommend that clinicians use a comprehensive assessment of converging evidence to make diagnostic decisions in DLLs in accordance with the American Speech-Language-Hearing Association's Code of Ethics. The content of this tutorial is most appropriate for Spanish–English DLLs between the ages of 4 and 8 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…For analysis, we divided participants into two groups: children with typical development; and children with LIs. Using converging evidence (e.g., standardized test scores and parent report) is best practice in identification of bilingual children with LI (Castilla-Earls et al, 2020; Sheng et al, 2012) and frequently a criteria threshold is used to operationalize LI in research with bilingual children (e.g., Gross & Kaushanskaya, 2020; Restrepo et al, 2013; Sheng et al, 2012). For the purpose of this research, we identified children with LI if they met two out of three of the following criteria: (a) received scores less than 85 (1 standard deviation from the mean) on the bilingual language index of the Bilingual English–Spanish Assessment (BESA; Peña et al, 2014); (b) had a previous diagnosis of LI from a speech–language pathologist; or (c) parents reported concern regarding their child’s language development on a demographic information form.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis, we divided participants into two groups: children with typical development; and children with LIs. Using converging evidence (e.g., standardized test scores and parent report) is best practice in identification of bilingual children with LI (Castilla-Earls et al, 2020; Sheng et al, 2012) and frequently a criteria threshold is used to operationalize LI in research with bilingual children (e.g., Gross & Kaushanskaya, 2020; Restrepo et al, 2013; Sheng et al, 2012). For the purpose of this research, we identified children with LI if they met two out of three of the following criteria: (a) received scores less than 85 (1 standard deviation from the mean) on the bilingual language index of the Bilingual English–Spanish Assessment (BESA; Peña et al, 2014); (b) had a previous diagnosis of LI from a speech–language pathologist; or (c) parents reported concern regarding their child’s language development on a demographic information form.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic assessment focuses on the child's learning potential rather than their performance and offers learning support for the child (Castilla-Earls et al, 2020). Because a child's potential to learn can be determined through interactions with more skilled individuals (Vygotsky, 1978), norm-referenced assessments that do not capitalize on such interactions may not capture true language ability.…”
Section: Da: Learning Potentialmentioning
confidence: 99%
“…De Lamo White and Jin's 4 review suggested that clinicians take a holistic approach to assessing bilingual children for DLD, including evaluating a child's language abilities within the context of their environment. Castilla-Earls et al's 3 review suggested that clinicians look for converging evidence from multiple sources when assessing bilingual children. Kay-Raining Bird et al's 2 review discussed bilingual children with developmental disorders more broadly and identified important differences between simultaneous and sequential bilinguals.…”
Section: Introductionmentioning
confidence: 99%